การเสริมสร้างกระบวนการฟื้นคืนสภาพด้วยกลุ่มบำบัดที่เน้นการหาทางออกในเยาวชนชายไทยที่ใช้สารเสพติดการศึกษานำร่อง - หลักทอง, สาวิตรี; นุจรี ไชยมงคล, นุจรี; เฮงอุดมทรัพย์, ภรภัทร (Journal of The Royal Thai Army Nurses, 2017)
การวิจัยกึ่งทดลองแบบกลุ่มเดียววัดผลก่อนและหลังการทดลองร่วมกับการติดตามผลครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาผลของการเสริมสร้างกระบวนการการฟื้นคืนสภาพในเยาวชนชายไทยที่ใช้สารเสพติดด้วยกลุ่มบำบัดที่เน้นการหาทางออก กลุ่มตัวอย่างคัดเลือกแบบเจาะจง จำนวน 8 คน เป็นเยาวชนชายไทยที่ใช้สารเสพติดในโรงเรียนวิวัฒน์พลเมือง จังหวัดชลบุรี เครื่องมือวิจัยได้แก่แบบวัดกระบวนการฟื้นคืนสภาพ มีค่าความเชื่อมั่นเท่ากับ .74 กลุ่มตัวอย่างได้เข้าร่วมกลุ่มบำบัดที่เน้นการหาทางออกเป็นระยะเวลา 6 สัปดาห์ๆ ละ 1 ครั้งๆ ละ 60-90 นาที ร่วมกับกิจกรรมตามปกติของโรงเรียน วิเคราะห์ข้อมูลโดยสถิติพรรณนาและสถิตินอนพาราเมตริก ผลการศึกษาพบว่ากลุ่มตัวอย่างมีค่าเฉลี่ยของกระบวนการฟื้นคืนสภาพในระยะหลังการเข้าร่วมกลุ่มบำบัดและระยะติดตามผลเพิ่มขึ้นกว่าในระยะก่อนเข้าร่วมกลุ่มบำบัดอย่างมีนัยสำคัญทางสถิติ จากผลการศึกษานี้มีข้อเสนอแนะว่ากลุ่มบำบัดที่เน้นการหาทางออกน่าจะเป็นอีกทางเลือกที่เหมาะสมเพื่อสร้างเสริมและคงสภาพของกระบวนการฟื้นคืนสภาพในเยาวชนชายไทยที่ใช้สารเสพติด Enhancing Recovery Process using Solution-Focused Group Therapy in Thai Male Youth Substance Abusers: A Pilot study A quasi-experimental design with one-group pretest-posttest with follow-up study aimed to determine the effect of enhancing recovery process in Thai male youth substance abusers by using Solution-Focused Group Therapy (SFGT). Purposive sampling for the pilot study was used to recruit eight Thai male youths with substance abuse in Wiwat Pollamuang school, Chon Buri province. A Thai version of the Recovery Process Inventory (RPI) was developed with Cronbach’s alpha of .74. The participants participated in a weekly SFGT for six weeks, 60-90 minutes per week and received the usual activity of the school. Descriptive statistics and two nonparametric tests were used to analyze the data. Results revealed that the participants had significantly higher RPI scores at posttest and follow-up periods than pretest. These findings indicate that SFGT may be an appropriate alternative way to enhance and maintain recovery process among Thai male youths with substance abuse.